Illuminating the Anticancerous Efficacy of a New Fungal Chassis for Silver Nanoparticle Synthesis - Aziz, Nafe; Faraz, Mohd; Sherwani, Mohd Asif; Fatma, Tasneem; Prasad, Ram (Frontiers in Chemistry, 2019)
Biogenic silver nanoparticles (Ag NPs) have supple platforms designed for biomedical and therapeutic intervention. Utilization of Ag NPs are preferred in the field of biomedicines and material science research because of their antioxidant, antimicrobial and anticancerous activity along with their eco-friendly, biocompatible and cost-effective nature. Here we present a novel fungus Piriformospora indica as an excellent source for obtaining facile and reliable Ag NPs with a high degree of consistent morphology. We demonstrated their cytotoxic property, coupled with their intrinsic characteristic that make these biogenic nanoparticles suitable for the anticancerous activity. In vitro cytotoxicity of biologically synthesized Ag NPs (BSNPs) and chemically synthesized Ag NPs (SNPs) was screened on various cancer cell lines, such as Human breast adenocarcinoma (MCF-7), Human cervical carcinoma (HeLa), Human liver hepatocellular carcinoma (HepG2) cell lines and embryonic kidney cell line (HEK-293) as normal cell lines. The antiproliferative outcome revealed that the BSNPs exhibited significant cytotoxic activity against MCF-7 followed by HeLa and HepG2 cell lines as compared to SNPs. The blend of cytotoxic properties, together with green and cost-effective characteristics make up these biogenic nanoparticles for their potential applications in cancer nanomedicine and fabrication coating of ambulatory and non-ambulatory medical devices.